Humoral immune response of cats to paragonimus infection - Quicho, Lucivic P.
Immunological study of host responses in Paragonimus infection in animal model may be an important approach to the elucidation of host-parasite relationships. The present study describes the serological reactions of sera obtained from ten cats infected with P. siamensis. P. siamensis was the specie of choice because of the ease in obtaining metacercaria. Although adult worms were found in the cats, no human cases have yet been reported. Sera from cats infected experimentally with 30 and 60 metacercaria o. P. siamensis were collected periodically and tested using enzyme-linked immuno assay (ELISA), complement fixation test (CFT), and immunoelectrophoresis (IEP). The antigen used was Chaffee-type antigen which was a crude veronal buffer extract of adult worms and was devoid of anti-complementary activity. The humoral immune response varied in individual animals during the course of infection. With ELISA and CFT, antibodies were detected as early as 2nd week after infection. On the other hand, none of the sera reacted with the antigen in immunoelectrophoresis. ELISA titers were consistently higher than CFT. The antibody response was not correlated to the infective dose and number of worms recovered. There was titer variability among cats infected with equal numbers of metacercaria for similar lengths of time and from which adult worms were recovered. However, relationship between the antibody levels and duration of infection was demonstrated. Cross reactions to unrelated parasites such as hookworm, Toxocara cati and Spirometra mansoni were not demonstated. The crude antigen faile to differentiate 2 species of Paragonimus. Positive P. siamensis and P. heterotremus sera gave cross reaction with the antigens prepared from homologous and heterologous adult worms. To the best of our knowledge, this is the first study of the development of humoral immune response in paragonimiasis employing ELISA technique. This paper has successfully applied ELISA in detecting antibodies against P. siamensis infection in cats. LUCIVIC P. QUICHO.